Aktorzy filmowi, aktorzy teatralni? Polski rynek aktorski ostatnich lat - DOMALEWSKI, ADAM (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
Film actors, theatre actors? The Polish actors’ market in recent years The author of the paper analyzes the career paths of Polish film and theater actors in recent years, taking account of social and institutional changes in Polish theater and cinema after 1989. On this basis, current three strategies present in the acting profession are identified: Courtier, Byplay and Celebrity. These three groups are highlighted depending on actors’ artistic achievements and accu- mulated symbolic capital. The main thesis of the article is that leading film actors, who are most successful on the big screen, forsake engagement in theater. While describing this regularity, the author provides specific examples of actresses and actors - eg. Magdalena Cielecka, Andrzej Chyra, Jacek Poniedziałek and Agnieszka Grochowska. The article concludes with considerations about the various reasons why Polands market for film actors and the theater market have split in recent years.